"Who can play this game?" The lived experiences of doctoral candidates and early career women in the neoliberal university. Issue 2 (3rd April 2018) - Caretta, Martina Angela; Drozdzewski, Danielle; Jokinen, Johanna Carolina; Falconer, Emily
Abstract: Work intensification is a characteristic of the current neoliberal trend in academia. Postgraduates and Early Career Researchers (PhD candidates and ECRs) in geography are no strangers to this development but are rarely the focus of publications or dialogue on the (gendered) outcomes of the academy's neoliberal agenda. Encouraged by the recent emotional turn in the social sciences and humanities, this article seeks to unveil some of the everyday particulars of life in academia for PhD candidates and ECRs under the tide of financial cuts and increased competition for funding. We explore the question: " Who can – and indeed wants to – play this game?" As three early and one mid-career academic women in four different institutions in the Global North, we make use of reflexivity, autobiographical writing, and reflection, to analyze increasingly stressful and demanding working conditions. Through the depiction of our lived experiences, we contend that the push for ever increasing outputs attends most of our time and represents a distinctly different form of scholarship than has been traditionally considered as the pathway into academia, not seldom jeopardizing well-being of young academics, one that needs to be interrogated by geographers.